Factors associated with perceived quality of life in older adults: ELSI-Brazil - Neri, Anita Liberalesso; Borim, Flávia Silva Arbex; Fontes, Arlete Portella; Rabello, Dóris Firmino; Cachioni, Meire; Batistoni, Samila Sathler Tavares; Yassuda, Mônica Sanches; Souza-Júnior, Paulo Roberto Borges de; Andrade, Fabiola Bof de; Lima-Costa, Maria Fernanda (Revista de Saúde Pública, 2019)
OBJECTIVE: To identify factors associated with perceived quality of life in a representative national sample of the population aged 50 or over. METHODS: Data from 7,651 participants of the baseline ELSI-Brazil (Brazilian Longitudinal Study of Aging), conducted between 2015 and 2016, were used. The perceived quality of life was measured by the CASP-19 scale - (CASP - control, autonomy, self-fulfillment and pleasure), considering the highest tertile as good quality of life. The independent variables included socio-demographic characteristics, mobility, loneliness, and indicators of sociability (social network, social support and social participation). The associations were tested using multivariate Poisson regression. RESULTS: The best perceived quality of life showed a positive and independent association with the frequency of contacts with friends (PR = 1.25 for at least once every 2–3 months and PR = 1.36 for at least once a week), instrumental support from spouse or partner in the household (PR = 1.69), and emotional support from other relatives (PR = 1.45), children or children in law (PR = 1.41) and spouse or partner (PR = 1.33). Negative associations were observed for participants aged 80 and over (RP = 0.77), with 4 to 7 or 8 or more years of schooling (PR = 0.78 and 0.75, respectively) and with difficulty in mobility (PR = 0.83). CONCLUSIONS: In addition to age and schooling, mobility, sociability and instrumental and emotional support are associated with perceived quality of life among older Brazilian adults. These characteristics must be considered when actions are taken, aiming to promote quality of life in this population.